Conversations with Christian Metz : Selected Interviews on Film Theory (1970-1991) - Fairfax, Daniel; Buckland, Warren (Book collections on Project MUSE., 2017)
"From 1968 to 1991 the acclaimed film theorist Christian Metz wrote several remarkable books on film theory. These books set the agenda of academic film studies during its formative period. Metz's ideas were taken up, digested, refined, reinterpreted, criticized and sometimes dismissed, but rarely ignored. This volume collects and translates into English a series of interviews with Metz, who offers readable summaries, elaborations, and explanations of his sometimes complex and demanding theories of film. We also discover the contents of his unpublished manuscript on jokes, his relation to Roland Barthes, and the social networks operative in the French intellectual community during the 1970s and 1980s."--Back cover.